Mechanisms of the cardioprotective effect of lithium - A. V. Mukhomedzyanov; E. V. Plotnikov; L. N. Maslov; V. I. Chernov; N. V. Naryzhnaya; A. S. Slidnevskaya; M. S. Yusubov; M. S. Larkina; A. A. Artamonov; M. V. Belousov (Бюллетень сибирской медицины)
Background. A study of the mechanisms of infarct size-limiting effects of lithium chloride (LiCl) on a model of myocardial infarction in vivo. Myocardial infarction is one of the main causes of death among the adult working population in economically developed countries. Currently, there are no drugs in clinical practice that would effectively protect the myocardium against ischemia – reperfusion injury, so there is a need to develop new drugs that can limit infarct size and reduce mortality. Aim. To study the mechanisms of infarct size-limiting effects of lithium chloride. Materials and methods. A study was performed in anesthetized Wistar rats with coronary artery occlusion (45 min) and reperfusion (120 min). The molecular mechanism of the protective effects of LiCl was examined in this model using appropriate blockers, including non-selective and selective blockers of ATP-sensitive potassium channel and NO synthase. Results. Administration of LiCl before ischemia significantly reduced infarct size as well as the as the incidence of ventricular arrhythmias. Administration of LiCl after ischemia also promoted a decrease in infarct size. NO synthase, cycloxigenase-2, protein kinase C, and endogenous opioids were not involved in the cardioprotective effect of lithium. The cardioprotective effect of LiCl is mediated via sarcolemmal ATP-sensitive potassium channel (sarcKATP channel) opening. Conclusion. LiCl reduced infarct size and prevented reperfusion cardiac injury. The main cellular ways of the infarct size-limiting effects of LiCl are mediated through the sarcKATP channel opening.